2004
DOI: 10.1159/000080392
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Quitting Serotonin Reuptake Inhibitor Therapy: Paradoxical Psychological Side Effects and Patient Satisfaction

Abstract: Background: The goal of this study was to document the existence of psychological side effects associated with serotonin reuptake inhibitors (SSRIs) taken for depression and to determine their relationship to patients’ decisions to stop treatment, and attitudes toward taking SSRIs again. Method: We conducted 161 semi-structured telephone interviews of adults who had completed a course of treatment for depression with one of the SSRIs. We identified 29 categories of unwanted psychological effects and analyzed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 7 publications
(11 reference statements)
3
29
0
6
Order By: Relevance
“…63 Serotonergic drugs can inhibit goal-directed behaviour, including sex, pleasurable exercise, and curiosity. 64 Norepinephrine. NE increases activation to both positive and negative stimuli.…”
Section: Midbrain Inputsmentioning
confidence: 99%
“…63 Serotonergic drugs can inhibit goal-directed behaviour, including sex, pleasurable exercise, and curiosity. 64 Norepinephrine. NE increases activation to both positive and negative stimuli.…”
Section: Midbrain Inputsmentioning
confidence: 99%
“…It is suggested that sexual dysfunction may contribute to patient noncompliance and this is important especially for the maintenance treatment of major depressive disorder (Bolling and Kohlenberg, 2004;Hirschfeld, 1999;Werneke et al, 2006). Quality of life is an important issue and includes sexual functioning (Williams et al, 2006) and concern about antidepressant-induced sexual dysfunction has continued to grow; however, the mechanism of action of sexual dysfunction associated with SSRIs is not well understood (Saiz-Ruiz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…And, as anybody who has studied ADM knows, management of ADM is a conflict-ridden business. Many patients are unwilling to take ADM; of those who do take it, many do not respond, while others who do respond develop intolerable side effects; finally, of those who respond with tolerable side effects, a good portion have their own ideas about how to take the medication and when to stop (Bolling & Kohlenberg, 2004).…”
Section: Resultsmentioning
confidence: 99%